"The City’s Charms and Challenges" by P K Leung (translation) - Chris Song (Writing Chinese: A Journal of Contemporary Sinophone Literature)
In this essay “The City’s Charms and Challenges” 城巿的诱惑·城市的挑战' by P K Leung (alias Ye Si 也斯) published in Zhong Hua Du Shu Bao (《 中华读书报》) in 2013, Leung traces his own journey as he -- just like many other Chinese families -- moved with his family from Guangdong to Hong Kong in 1949, where he grew up, lived and taught, becoming one of the best-known Hong Kong writers. In the essay, he also mapped out the early beginnings of Hong Kong literature, its intrinsic roots in Chinese literature, and how it has thrived amidst the socio-cultural and historical changes in Hong Kong in the last few decades. In charting the locality of places, the difference between the urban and the rural living in Hong Kong, Leung highlights the importance to acknowledge the complex layers and dimensions of Hong Kong literature, where both Chinese and English languages and different cultures intersect.